Sand Castle Bay - Woods, Sherryl (Don Mills, Ont. : Harlequin MIRA, 2013)
Now a widower with a young son, Boone has a second chance with Emily when a storm brings her home. But with his former in-laws threatening a custody suit, the stakes of loving her are higher than ever. Will fate once again separate them--or is the time finally right for these two star-crossed lovers?
Keywords: Man-woman relationships -- Fiction; Love stories